Metal loading effects on carbon-supported Pd electrocatalysts - Ciapina, E. G. [UNESP]; Viana, L. B. [UNESP]; Santos, R. M.I.S. [UNESP]; Nogueira, M. S.M. [UNESP]; Almeida-Júnior, O. P. [UNESP]; Nunes, R. S. [UNESP]; Santos, S. F.; Nakazato, R. Z. [UNESP] (Elsevier, 2018)
We report for the first time effects of altering the amount of Pd supported on high-surface area carbon (Pd/C). Cyclic voltammetry in 0.1 M H2SO4 using Pd/C electrocatalysts with distinct metal-to-carbon ratio, Pd black and a Pd wire electrodes reveals unambiguously metal loading effects, such as a decrease in the peak potential for the reduction of palladium oxide (PdO), an increase of the charges of desorption of hydrogen, and formation/reduction of PdO with the Pd content. Such effects need to be taken into account when designing Pd-based Fuel Cells electrocatalysts.
Keywords: Carbon; Cyclic voltammetry; Electrocatalysts; Metal loading; Palladium